Evaluación ginecológica, subfertilidad, gestación y llegada accidentalmente al sacrificio en bovinos - Gaibor Baldeon, Joel Joshue (2022)
The present investigation was carried out with the objective of carrying out a gynecological evaluation, subfertility, gestation and accidental arrival at the slaughter of bovines in the Municipal Camal of the city of Riobamba, which lasted one month and seven days. Ultrasounds and palpations were performed on discarded cows, prior to slaughter, where the revised uteruses were classified as empty or pregnant, for which an experimental design was not used, but rather descriptive statistics were used for the interpretation of the data, as well as a frequency distribution for the qualitative variables. In addition, pregnancy was determined in discard cattle, where the results obtained showed that cows that were physiologically well represented 21.3%; on the other hand, it was found that 17.3% of cows that were slaughtered in a state of pregnancy due to ignorance of the farmers and finally the cows slaughtered for presenting related or indirect pathologies between pregnant and empty represented 30.6%.